(untitled) (Experimental biology, 2015)
In this work studied the viability and activity of oxidizing and cellulolytic bacteria and comparison of methods of storage. Installed that the oil-oxidizing activity of cultures laid in storage varies in different ways. Showed a high viability oxidizing bacteria after years of storage by drying, utilization oil was higher than when stored in other ways. Check of activity cellulolytic bacteria after years of storage in different ways showed that all cultures were active at different storage methods, except for storage in the soil. The highest activity of cultures was observed in method of storage lyophilization (diameter growth inhibition was 30-38mm).